Формування лідерських якостей майбутніх педагогів закладів позашкільної освіти засобами студентського самоврядування - Лебедик, Леся Вікторівна; Блоха, Олександр (Національний технічний університет "Харківський політехнічний інститут", 2024)
Розглянуто актуальну проблему формування лідерських якостей майбутніх педагогів закладів позашкільної освіти засобами студентського самоврядування. Обґрунтовано доведено, що ефективність досліджуваного процесу забезпечує дотримання і реалізація виокремлених ними основних шести педагогічних умов. Розкрито суттєві перешкоди для зростання ролі студентського самоврядування у професійній підготовці майбутніх педагогів закладів позашкільної освіти: недостатній рівень сформованості у них важливих лідерських якостей і відсутність у майбутніх педагогів навичок щодо саморозвитку лідерських якостей в умовах студентського самоврядування. Зроблено висновок про необхідність подальшого пошуку й удосконалення шляхів формування лідерських якостей майбутніх педагогів закладів позашкільної освіти засобами студентського самоврядування з метою вироблення перспективних освітньопрофесійних програм їхньої підготовки.

The article is devoted to the actual problem of forming the leadership qualities of future teachers of out-of-school education institutions by means of student self-government. The authors reasonably prove that the effectiveness of the researched process ensures the observance and implementation of the main six pedagogical conditions identified by them. The study revealed significant obstacles to the growth of the role of student selfgovernment in the professional training of future teachers of extracurricular education institutions: insufficient level of formation of important leadership qualities in them and the lack of skills of future teachers regarding the self-development of leadership qualities in the conditions of student self-government. It was concluded that it is necessary to further search for and improve ways of forming the leadership qualities of future teachers of extracurricular education institutions by means of student self-government in order to develop promising educational and professional programs for their training.
Formation of leadership qualities of future teachers of extra-school education institutions by means of student selfgovernment
Keywords: лідерські якості; студентське самоврядування; позашкільна освіта; підготовка педагогів; leadership qualities; student self-government; extracurricular education institutions; training of teachers